Case report: Early carotid stent shortening in patient with radiation-induced carotid stenosis - Choi, Woochan; Hwang, Yang-Ha; Kim, Yong-Won (Frontiers in Neurology, 2023)
Carotid artery stenting (CAS) for carotid stenosis has been widely used as an alternative treatment in patients not eligible for surgery. The shortening of a carotid stent rarely occurs. We report a case of early shortening of CAS in a patient with radiation-induced carotid stenosis and discuss the potential pathophysiology and strategies for prevention. This case presents a 67-year-old male who underwent radiotherapy for oral cavity squamous cell carcinoma 7 years ago and subsequently developed severe stenosis in the left proximal internal carotid artery. The patient underwent CAS for symptomatic severe carotid stenosis. Follow-up CT angiography revealed shortening of the carotid stent, and additional carotid stenting was performed. We speculate that the possible mechanism of early complication of CAS could be slippage and shortening of the stent due to weak anchoring between the stent strut and the fibrotic arterial wall in radiation-induced carotid stenosis.